Dining from the coast to the summit: Salmon and pine nuts determine the summer body condition of female brown bears on the Shiretoko Peninsula - Yuri Shirane; Mina Jimbo; Masami Yamanaka; Masanao Nakanishi; Fumihiko Mori; Tsuyoshi Ishinazaka; Mariko Sashika; Toshio Tsubota; Michito Shimozuru (Ecology and Evolution, 2021)
Abstract Body condition in mammals fluctuates depending on energy intake and expenditure. For brown bears (Ursus arctos), high‐protein foods facilitate efficient mass gain, while lipids and carbohydrates play important roles in adjusting dietary protein content to optimal levels to maximize energy intake. On the Shiretoko Peninsula, Hokkaido, Japan, brown bears have seasonal access to high‐lipid pine nuts and high‐protein salmon. To assess seasonal and annual fluctuation in the body condition of adult female brown bears in relation to diet and reproductive status, we conducted a longitudinal study in a special wildlife protection area on the Shiretoko Peninsula during 2012–2018. First, analyses of 2,079 bear scats revealed that pine nuts accounted for 39.8% of energy intake in August and salmon accounted for 46.1% in September and that their consumption by bears varied annually. Second, we calculated the ratio of torso height to torso length as an index of body condition from 1,226 photographs of 12 adult females. Results indicated that body condition continued to decline until late August and started to increase in September when salmon consumption increased. In addition, body condition began to recover earlier in years when consumption of both pine nuts and salmon was high. Furthermore, females with offspring had poorer body condition than solitary females, in particular in late August in years with low salmon consumption. Our findings suggest that coastal and subalpine foods, which are unique to the Shiretoko Peninsula, determine the summer body condition of female brown bears, as well as their survival and reproductive success.